Targeted sequencing identifies novel variants in common and rare MODY genes. Issue 12 (8th October 2019) - de Santana, Lucas S.; Caetano, Lilian A.; Costa‐Riquetto, Aline D.; Franco, Pedro C.; Dotto, Renata P.; Reis, André F.; Weinert, Letícia S.; Silveiro, Sandra P.; Vendramini, Marcio F.; do Prado, Flaviene A.; Abrahão, Giovanna C. P.; de Almeida, Ana Gregória F. P.; et al.
Abstract: Background: Maturity‐onset diabetes of the young (MODY) is a form of monogenic diabetes with autosomal dominant inheritance. To date, mutations in 11 genes have been frequently associated with this phenotype. In Brazil, few cohorts have been screened for MODY, all using a candidate gene approach, with a high prevalence of undiagnosed cases (MODY‐X). Methods: We conducted a next‐generation sequencing target panel (tNGS) study to investigate, for the first time, a Brazilian cohort of MODY patients with a negative prior genetic analysis. One hundred and two patients were selected, of which 26 had an initial clinical suspicion of MODY‐ GCK and 76 were non‐ GCK MODY. Results: After excluding all benign and likely benign variants and variants of uncertain significance, we were able to assign a genetic cause for 12.7% (13/102) of the probands. Three rare MODY subtypes were identified ( PDX1 / NEUROD1 / ABCC8 ), and eight variants had not been previously described/mapped in genomic databases. Important clinical findings were evidenced in some cases after genetic diagnosis, such as MODY‐ PDX1 / HNF1B . Conclusion: A multiloci genetic approach allowed the identification of rare MODY subtypes, reducing the large percentage of MODY‐X in Brazilian cases and contributing to a better clinical, therapeutic, and prognostic characterization of these rare phenotypes. Abstract : Maturity‐onset diabetes of the young (MODY) is a form of monogenic diabetes with autosomal dominant inheritance and, to date, mutations in 11 genes have been frequently associated with this phenotype. We have conducted a NGS target panel (tNGS) study to investigate, for the first time, a Brazilian cohort of MODY patients with a negative prior genetic analysis. One hundred and two patients were selected and we were able to assign a genetic cause for 12.7% (13/102) of the probands, with three rare MODY subtypes were identified (PDX1/NEUROD1/ABCC8).